Effect of organic amine alkali and inorganic alkali on benzotriazole removal during post Cu-CMP cleaning *Project supported by the Major National Science and Technology Special Projects (No. 2016ZX02301003-004-007), the Natural Science Foundation, China (No. 61704046), and the Hebei Natural Science Foundation Project (No. F2018202174). (December 2018) - Yang, Liu; Tan, Baimei; Liu, Yuling; Gao, Baohong; Liu, Yilin; Han, Chunyu; Wang, Qi; Tian, Siyu
Abstract: Benzotriazole (BTA), an anticorrosion agent of slurry, is the main organic pollutant remaining after CMP of multilayer copper wiring, and also the main removal object of post CMP cleaning. The adsorption of BTA onto the copper could form a dense Cu-BTA film, which makes the copper surface strongly passivated. According to this characteristic, quantitative analysis of BTA residue after cleaning is carried out by contact angle measurement and electrochemical measurement in this paper. A scanning electron microscope (SEM) with EDX was used to observe and analyze the BTA shape and elements. The efficiencies of organic alkali and inorganic alkali on the removal of BTA were studied. The corresponding reaction mechanism was also analyzed. The results show that the adsorption structure of Cu(I)-BTA cannot be destroyed in an alkaline environment with a pH less than 10; the effect of BTA removal by inorganic alkali is worse than that of the organic amine alkali with the coordination structure under the same pH environment; the FA/O II chelating agent with the fraction of 200 ppm can effectively remove BTA residue on the surface of copper wafer.